2020
DOI: 10.22541/au.160226405.50599698/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of ten years of social oocyte cryopreservation: a research article

Abstract: Objective: To assess the relationship between number of oocytes retrieved during social egg freezing (SEF) cycles with various clinical, biochemical and radiological markers; e.g. age, body mass index (BMI), baseline anti-Mullerian hormone (AMH), antral follicle count (AFC), Oestradiol level (E2) and total number of follicles [?]12mm at trigger. Main outcome measures: To describe the characteristics and outcomes of women who underwent SEF. Methods: A retrospective cohort of women embarking on SEF between 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As the process is still novel, only 3.1–12.1% of women who have undergone the procedure have since returned to use their cryopreserved oocytes ( Ben-Rafael, 2018 ; Cobo et al , 2018 ; Gürtin et al , 2019 ; Kasaven et al , 2020 ). Consequently, successful LBRs of 17.5–30.5% have been observed in such women ( Gürtin et al , 2019 ; Kasaven et al , 2020 ), highlighting that EOC is a feasible method of fertility preservation for ARFD. The chances of successful livebirth are dependent on two factors; age at the time of cryopreservation and the number of oocytes retrieved.…”
Section: Elective Oocyte Cryopreservationmentioning
confidence: 99%
“…As the process is still novel, only 3.1–12.1% of women who have undergone the procedure have since returned to use their cryopreserved oocytes ( Ben-Rafael, 2018 ; Cobo et al , 2018 ; Gürtin et al , 2019 ; Kasaven et al , 2020 ). Consequently, successful LBRs of 17.5–30.5% have been observed in such women ( Gürtin et al , 2019 ; Kasaven et al , 2020 ), highlighting that EOC is a feasible method of fertility preservation for ARFD. The chances of successful livebirth are dependent on two factors; age at the time of cryopreservation and the number of oocytes retrieved.…”
Section: Elective Oocyte Cryopreservationmentioning
confidence: 99%
“…Single women who do not want to conceive can postpone childbearing by cryopreserving oocytes. It was reported that an increasing number of women pursue oocyte cryopreservation [ 5 ] and the median age of these women is 38 years [ 6 , 7 ]. Of note, more than half the women who undergo oocyte cryopreservation are older than 37 years.…”
Section: Introductionmentioning
confidence: 99%